2018
DOI: 10.3390/ijms19030893
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Growth Hormone for Adults with Growth Hormone Deficiency Syndrome: Benefits and Risks

Abstract: Pharmacological treatment of growth hormone deficiency (GHD) in adults began in clinical practice more than 20 years ago. Since then, a great volume of experience has been accumulated on its effects on the symptoms and biochemical alterations that characterize this hormonal deficiency. The effects on body composition, muscle mass and strength, exercise capacity, glucose and lipid profile, bone metabolism, and quality of life have been fully demonstrated. The advance of knowledge has also taken place in the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 122 publications
(144 reference statements)
0
28
0
5
Order By: Relevance
“…There is no doubt that this treatment improves the condition of patients, and can even reverse most signs and symptoms of this hormonal deficiency. However, chronic GH administration may be associated with risks of increasing BMI, waist circumference, waist–hip ration, and even cardiovascular risk markers [19].…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that this treatment improves the condition of patients, and can even reverse most signs and symptoms of this hormonal deficiency. However, chronic GH administration may be associated with risks of increasing BMI, waist circumference, waist–hip ration, and even cardiovascular risk markers [19].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Moreover, evidence from adult patients treated with GH replacement therapy suggests that recombinant human GH (rhGH) treatment does not increase the rate of recurrence or progression of hypothalamic–pituitary tumors, compared with similar patients who did not receive rhGH treatment. 6 , 7 However, in adult patients with GHD who were childhood cancer survivors and received rhGH treatment in childhood, there may be an increased risk of secondary malignancies versus the general population. 7 10 The Safety and Appropriateness of Growth Hormone Treatments in Europe study suggested possible effects of rhGH therapy on bone cancer, bladder cancer and Hodgkin lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 However, in adult patients with GHD who were childhood cancer survivors and received rhGH treatment in childhood, there may be an increased risk of secondary malignancies versus the general population. 7 10 The Safety and Appropriateness of Growth Hormone Treatments in Europe study suggested possible effects of rhGH therapy on bone cancer, bladder cancer and Hodgkin lymphoma. 10 In the same cohort, although cancer incidence risk was unrelated to duration or cumulative dose of rhGH treatment, cancer mortality risk in patients with previous cancer increased significantly with increasing daily rhGH dose ( p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, various studies have provided relevant information on the efficacy and safety of GH therapy in patients with AGHD. The knowledge acquired during this time has been compiled into different guidelines that offer clinicians an evidence‐based, practical approach for the management of AGHD …”
Section: Introductionmentioning
confidence: 99%
“…The knowledge acquired during this time has been compiled into different guidelines that offer clinicians an evidence-based, practical approach for the management of AGHD. 3 In comparison with normal individuals, patients with AGHD have reduced lean body mass and muscle strength. 4 Loss of skeletal muscle mass and consequent loss in muscle function has been associated with negative impacts on the activities of daily living and increases patients' frailty and likelihood to fall.…”
Section: Introductionmentioning
confidence: 99%